2014
DOI: 10.4103/0976-0105.139731
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern and efficacy of anti-diabetic drugs in maintaining optimal glycemic levels in diabetic patients

Abstract: Context:Despite the availability of efficacious anti-diabetic drugs, which act by different mechanisms to reduce the blood-glucose, the majority of people with diabetes on anti-diabetic drug therapy, have poor glycemic control and diabetic vascular complications.Aim and Objectives:The aim was to study the prescribing pattern and efficacy of anti-diabetic drugs in maintaining optimal glycemic levels in diabetic patients attending tertiary care teaching hospital in Navi Mumbai.Materials and Methods:A prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 19 publications
7
70
2
4
Order By: Relevance
“…15,16 Worldwide, studies on medication adherence among diabetic patients have shown a wide variation. [17][18][19][20][21][22][23][24] In India, [25][26][27] Limited studies from Southern and Northern regions of India have documented wide variation in the medication adherence and have addressed the issues of nonadherence in diabetic patients. 21,[28][29][30][31][32][33] AIM Therefore, this study was conducted to assess the medication adherence among type II diabetic patients attending a tertiary care hospital in Navi Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Worldwide, studies on medication adherence among diabetic patients have shown a wide variation. [17][18][19][20][21][22][23][24] In India, [25][26][27] Limited studies from Southern and Northern regions of India have documented wide variation in the medication adherence and have addressed the issues of nonadherence in diabetic patients. 21,[28][29][30][31][32][33] AIM Therefore, this study was conducted to assess the medication adherence among type II diabetic patients attending a tertiary care hospital in Navi Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%
“…Increased insulin use was also observed in many other studies. 19 Additionally, the use of DPP-4i was found to have significant importance in therapy. There were studies published that use of DPP-4i in both dual and triple therapy is safe and efficacious option.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Hasil ini senada dengan penelitian RS Mumbai India pada 100 pasien DM tipe 2 yang sebagian besar (56,4%) mendapatkan terapi OAD dibanding insulin (43,6%), namum pada penelitian ini terapi tunggal OAD lebih banyak digunakan dibandingkan kombinasi. 8 Penelitian ini juga mendapatkan hasil OAD oral terbanyak digunakan sebagai terapi adalah metformin (90,3%), diikuti oleh golongan pemicu sekresi insulin yaitu sulfonilurea. Metformin merupakan OAD dari golongan penghambat glukoneogenesis.…”
Section: Pembahasan Gambaran Penggunaan Obat Anti Diabetikum (Oad)unclassified
“…Golongan penghambat glukoneogenesis dapat memperbaiki ambilan glukosa sebesar 10-40%, mengurangi glikogenolisis dan glukoneogenesis sehingga dapat menurunkan kadar glukosa hati. 3,8 Hal ini berbeda dengan penelitian Mumbai india didapatkan penggunaan golongan penghambat glukoneogenesis di rumah sakit urutan kedua setelah sulfonilurea. 8 Dosis harian metformin tersering digunakan pada penelitian ini adalah 1000 -1500 mg. Penggunaan metformin dimulai dari dosis 500 mg 2 x/hari atau 850 mg 1 x/hari.…”
Section: Pembahasan Gambaran Penggunaan Obat Anti Diabetikum (Oad)unclassified